PELATIHAN DAN PENDAMPINGAN PENGELOLAAN POTENSI DESA SEBAGAI UPAYA PENCAPAIAN SDGs - Muhammad Mukhtar (Jambura Journal of Husbandry and Agriculture Community Serve (JJHCS), 2021)
The purpose of the Thematic Village Community Service Program is to increase the knowledge and skills of the community in processing and utilizing surrounding food crops into food that has high economic value. The output that will be produced is in the form of processed food derived from ginger and moringa. The Thematic KKN-Thematic to build this village has been carried out in Bubode Village, Tomilito District. Several program activities that have been carried out at the location of the activity are the program for making Garbage Trays, Village Boundaries and PKK Hearts. The method used is empowering the target group including learning techniques in the form of providing theory and simulation to the target community and then direct practice with students and the community. Keywords: SDGs, Community Empowerment